Identifying seedling root architectural traits associated with yield and yield components in wheat - Xie, Quan; Fernando, K.M.C.; Mayes, Sean; Sparkes, Debbie L. (Oxford Journals, 2017)
Background and Aims: Plant roots growing underground are critical for soil resource acquisition, anchorage and plant-environment interactions. In wheat (Triticum aestivum), however, the target root traits to improve yield potential still remain largely unknown. This study aimed to identify traits of seedling root system architecture (RSA) associated with yield and yield components in 226 recombinant inbred lines (RILs) derived from a cross between the bread wheat Triticum aestivum ‘Forno’ (small, wide root system) and spelt Triticum spelta ‘Oberkulmer’ (large, narrow root system). Methods: A ‘pouch and wick’ high-throughput phenotyping pipeline was used to determine the RSA traits of 13-d-old RIL seedlings. Two field and one glasshouse experiments were carried out to investigate the yield, yield components and phenology, followed by identification of quantitative trait loci (QTL). Key Results: There was substantial variation in RSA traits between genotypes. Seminal root number and total root length were both positively associated with grains m-2, grains per spike, above-ground biomass m-2, and grain yield. More seminal roots and longer total root length were also associated with delayed maturity and extended grain filling, likely to be a consequence of more grains being defined before anthesis. Additionally, the maximum width of the root system displayed positive relationships with spikes m-2, grains m-2, and grain yield. Ten RILs selected for longest total roots exhibited the same effects on yield and phenology as described above, compared to the ten lines with shortest total roots. Genetic analysis revealed 38 QTL for the RSA, and QTL coincidence between the root and yield traits were frequently observed, indicating tightly linked genes or pleiotropy, which concurs with the results of phenotypic correlation analysis. Conclusions: Based on the results from the Forno × Oberkulmer population, it is proposed that vigorous early root growth, particularly more seminal roots and longer total root length, is important to improve yield potential, and should be incorporated into wheat ideotypes in breeding.